A challenging case of fenofibrate induced neutropenia - Pula Lakshmi, Bindumathi; Peddareddy, Spandana; Murali, N. Aditya; Rajagopal, Swati (International Journal of Research in Medical Sciences, 2022)
Fenofibrate induced neutropenia is a rare condition. We reported 59-year-old male who developed neutropenia after taking fenofibrate for 20 days. He presented with complaints of fever, upper respiratory tract infection (URTI) symptoms. At presentation his total counts were 800. He was evaluated thoroughly for other causes of neutropenia and was treated with antibiotics, steroids, G-CSF. Once the fenofibrate was stopped, patient counts improved and his symptoms subsided. Hence, it is very important to always keep in mind the possibility of side effects of drugs, however remotely rare they are.